2021
DOI: 10.21203/rs.3.rs-392565/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes of Entropy Connectivity of the Default Mode and Central Executive Networks in ASD

Abstract: Background: Autism spectrum disorder (ASD) is a heterogeneous disorder characterized by different levels of repetitive and stereotypic behavior as well as cognitive deficit. Brain structural and functional changes of individuals with ASD have been reported in previous investigations. To provide more implications for clinical diagnosis and treatment of ASD, it is necessary to further explore the changes of cerebral neural activities in ASD.Method: We reinvestigate the brain functional networks (viz. the default… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Transfer entropy (TE) is an extension of the concept of mutual information, which is based entropy to infer quantified information transfer (Schreiber, 2000 ). For example, Zhao et al ( 2021 ) found the decreased causal connectivity from right ventral posterior cingulate cortex to right ventral anterior cingulate cortex and increased causal connectivity from right dorsal frontal cortex to left piriform cortex within the DMN in ASD using entropy connectivity. Dejman et al ( 2017 ) also found a significant difference in average degree between HC and ASD groups during a passive face processing task by integrating transfer entropy and graph theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer entropy (TE) is an extension of the concept of mutual information, which is based entropy to infer quantified information transfer (Schreiber, 2000 ). For example, Zhao et al ( 2021 ) found the decreased causal connectivity from right ventral posterior cingulate cortex to right ventral anterior cingulate cortex and increased causal connectivity from right dorsal frontal cortex to left piriform cortex within the DMN in ASD using entropy connectivity. Dejman et al ( 2017 ) also found a significant difference in average degree between HC and ASD groups during a passive face processing task by integrating transfer entropy and graph theory.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer entropy (TE) is an extension of the concept of mutual information, which is based entropy to infer quantified information transfer (Schreiber, 2000). For example, Zhao et al (2021) (2017) also found a significant difference in average degree between HC and ASD groups during a passive face processing task by integrating transfer entropy and graph theory.…”
Section: Introductionmentioning
confidence: 99%